Dermal Flap Advancement Combined with Conservative Sphincterotomy in the Treatment of Chronic Anal Fissure. Issue 2 (February 2015) - Theodoropoulos, George E.; Spiropoulos, Vasileios; Bramis, Konstantinos; Plastiras, Aris; Zografos, George
Lateral internal sphincterotomy (LIS) is considered the surgical treatment of choice for chronic anal fissure (CAF). Flap techniques for fissure coverage have the advantage of primary wound healing, potentially providing better functional results and faster pain relief. The standard surgical strategy for CAF consisting of conventional LIS (CLIS) up tothe dentate line was modified by "tailoring" the LIS to the apex of the CAF, but never greater than 1 cm, and by advancing a dermal flap for coverage of the CAF (LIS + flap) after fissurectomy. Thirty consecutive patients who underwent "LIS + flap" were compared with 32 patients who had been previously treated by CLIS. A modified, trapezoidlike Y-V flap from perianal skin was advanced into the CAF base. Pain at the first postoperative day, pain at defecation during the first week, postoperative use of analgesics, and time for patients' pain relief were significantly less at the "LIS + flap" group ( P < 0.01). Objective healing was achieved faster ( P < 0.01) and soiling episodes were less ( P < 0.05) after "LIS + flap." The addition of a dermal flap after "conservative" LIS resulted in better healing and significantly less postoperative discomfort than the isolated application of CLIS.